Czech Minority in a Slovak City: Identity and Memory: (A Case Study from Bratislava) - Luther, Daniel (Lidé města, 2008)
On the model example of the Czech community, this paper focuses on the formation of the collective identity of an ethnic minority in a present-day city. The emergence of the community, its development in the 1st half of the 20th century as well as the forced departure of most of the residents of Czech nationality from the city during WW II have been firmly etched in the historical memory of the minority members and represent the cornerstones of their identity. In the 2nd half of the 20 century, processes of integration and assimilation took place. Revitalization of the Czech community after the division of Czechoslovakia points to the importance of macro-social processes in the formation of minority communities.